A 58S bioactive glass for dentin hypersensitivity and erosive tooth wear: An in vitro study. (December 2022) - Viana, Ítallo Emídio Lira; Borges, Roger; Marchi, Juliana; Feitosa, Sabrina; Marques, Márcia Martins; Scaramucci, Taís
Highlights: Morphology and composition of a 58S bioactive glass targets dentin hypersensitivity. Bioactive glass decreases dentin permeability after application. Bioactive glass reduces dentin permeability after cycling. Bioactive glass does not protect dentin against erosive tooth wear. Abstract: Objectives: To assess the effect of an experimental 58S bioactive glass on dentin permeability (dP) and erosive tooth wear (dentin surface loss - dSL). Methods: 58S bioactive glass was synthetized using a sol-gel methodology, following by lyophilization and calcination, then mixed with phosphoric acid to obtain a paste (BGP). Forty-eight dentin disks (1 mm-thick) were used for dP, and 48 dentin slabs (3 mm × 3 mm) for dSL, which were assessed at three time intervals: post-EDTA (5 min in 17% EDTA solution); post-treatment (C: distilled water; BGP: experimental bioactive glass paste; NP: Nupro prophylaxis paste; CXT: Clinpro XT varnish); and post-erosive/abrasive cycling. Data were statistically analyzed (α=0.05). Results: For dP and dSL, Groups did not differ significantly post-EDTA (p>0.05). Post-treatment, all groups showed lower dP than C (p<0.05), without differing significantly among them. For the dSL analysis, Groups C, BGP and NP did not differ significantly, showing lower values than CXT (p<0.05). Post-cycling, C continued to show the highest dP (p<0.05). Specimens from Group CXT had the lowest dP and did not differ from NP (p=0.86) which did not differ from BGP (p=0.193). For C and BGP, dP value was higher post-cycling than post-treatment (p<0.05). For NP and CXT, these experimental times did not differ (p>0.05). Post-cycling, dSL for C, BGP and NP did not differ significantly; values were higher than those for CXT (p<0.05). Conclusions: BGP reduced dP after application, with a reduced effect after cycling. Nonetheless, it was not able to protect dentin against erosive tooth wear. Clinical Significance: Minimizing dentin hypersensitivity is a challenge in the field of dentistry. The development of alternative products with potential to obliterate dentinal tubules and provide resistance to chemical/mechanical stimuli is, thus, highly desirable. We have proposed a material able to reduce dentin permeability, which has emerged as a promising alternative for this purpose.